2021
DOI: 10.3390/foods10081696
|View full text |Cite
|
Sign up to set email alerts
|

Functionality and Palatability of Yogurt Produced Using Beetroot Pomace Flour Granulated with Lactic Acid Bacteria

Abstract: Following the idea of sustainability in food production, a yogurt premix based on beetroot (Beta vulgaris) pomace flour (BPF) was developed. BPF was granulated with lactose solution containing lactic acid bacteria (LAB) by a fluidized bed. Particle size increased ~30%. A decrease in Carr Index from 21.5 to 14.98 and Hausner ratio from 1.27 to 1.18 confirmed improved flowability of granulated BPF, whereas a decrease in water activity implied better storability. Yogurts were produced weekly from neat starters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(82 reference statements)
2
7
0
Order By: Relevance
“…However, cells were most susceptible to an extract obtained from yogurt supplemented with GW (up to 25% inhibition of the cell viability). Similarly to obtained results, in our previous research, it was pointed out that yogurt-extracted whey inhibited HCT116 cell viability to some extent (Jovanović et al 2021). More pronounced inhibition of colon cancer cell viability could be accomplished by increasing the dose of GW and adding additional probiotic strains or parabiotics at the beginning of yogurt preparation.…”
Section: Lab Viabilitysupporting
confidence: 82%
See 2 more Smart Citations
“…However, cells were most susceptible to an extract obtained from yogurt supplemented with GW (up to 25% inhibition of the cell viability). Similarly to obtained results, in our previous research, it was pointed out that yogurt-extracted whey inhibited HCT116 cell viability to some extent (Jovanović et al 2021). More pronounced inhibition of colon cancer cell viability could be accomplished by increasing the dose of GW and adding additional probiotic strains or parabiotics at the beginning of yogurt preparation.…”
Section: Lab Viabilitysupporting
confidence: 82%
“…In situ anti-Escherichia activity. Anti-Escherichia activity was investigated as previously described by Jovanović et al (2021). Escherichia strains: E. coli 0157: H7 and E. coli ATCC 35218 were incubated in MHB at 37 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Marchiani et al (2016) [ 63 ], whereby the overall acceptability scores of the grape pomace yogurt were higher than the scores of a control yogurt. Jovanovic´ et al (2021) [ 64 ] also demonstrated an acceptable palatability of yogurt, with the addition of granulated beetroot pomace flour.…”
Section: Resultsmentioning
confidence: 99%
“…The pH values of T1 were found to be significantly lower than those of other treatment groups ( p < 0.05). As per Jovanović M et al (2021) [ 19 ], lactic strains possess the ability to ferment lactose into lactic acid, which leads to an increase in acidity and a decrease in the pH of yogurt. The production of lactic acid ultimately results in a reduction in pH.…”
Section: Resultsmentioning
confidence: 99%